PENGARUH AKTIVITAS PENGASUHAN CUCU TERHADAP FUNGSI KOGNITIF PADA PEREMPUAN LANSIA - Frederica Jovianti,* Linda Suryakusuma,* Yuda Turana,* Yvonne Suzy Handajani* (NEURONA, 2018)
INTRODUCTION COGNITIVE IMPAIRMENT IS A NEURODEGENERATIVE PROCESS WHICH OFTEN EXPERIENCED BY THE ELDERLY ONE OF THE FACTORS ASSOCIATED WITH COGNITIVE FUNCTION IS GRANDPARENTING WHICH IS COMMON AND HAS BECOME A SOCIAL NORM IN INDONESIA